2016
DOI: 10.18632/oncotarget.11500
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNA profiles: identification of miR-23a as a novel biomarker for chemoresistance in esophageal squamous cell carcinoma

Abstract: BACKGROUNDThis study aims to explore novel microRNAs in plasma for predicting chemoresistance in preoperative chemotherapy of patients with esophageal squamous cell carcinoma (ESCC) using a microRNA array-based approach.RESULTS(1) Four candidate microRNAs (miR-223, 103a, 23b and 23a), which were highly expressed in the pretreatment plasma of patients with a low histopathologic response, were selected. (2) In a large-scale validation analysis by quantitative RT–PCR, plasma levels of miR-223, miR-23b and miR-23a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 76 publications
2
54
1
1
Order By: Relevance
“…miRNA-152 and miRNA-185 were demonstrated to be significantly downregulated in SKOV3/DDP and A2780/DDP cells (14). Previous studies have demonstrated that miRNA-21 is involved in drug resistance in multiple types of cancer, including gastric, breast and lung cancer, via regulation of PTEN (7,8,15). In the present study, the expression level of miRNA-21 in SKOV3/DDP cells was significantly higher than in SKOV3 cells, as detected by qPCR.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…miRNA-152 and miRNA-185 were demonstrated to be significantly downregulated in SKOV3/DDP and A2780/DDP cells (14). Previous studies have demonstrated that miRNA-21 is involved in drug resistance in multiple types of cancer, including gastric, breast and lung cancer, via regulation of PTEN (7,8,15). In the present study, the expression level of miRNA-21 in SKOV3/DDP cells was significantly higher than in SKOV3 cells, as detected by qPCR.…”
Section: Discussionsupporting
confidence: 52%
“…Multiple previous reports have indicated that dysregulation of miRNA target genes promotes drug resistance, and inhibition of miRNAs may reverse drug resistance (2,3). miRNA-21 is overexpressed in multiple types of cancer, and promotes the initiation of cancer, progression and drug-resistance (4)(5)(6)(7)(8)(9). miRNA-21 impacts tumorigenesis by negatively regulating several targets.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some extracellular miRNAs occur not only through cell lysis but also through active secretion [25][26][27] and can function as intercellular transmitters 19,26,28,29 . Thus, various blood-based miRNAs have been identified, including those in this study, and can be used for cancer detection, monitoring tumor dynamics, and predicting prognosis and chemoresistance [30][31][32][33][34][35][36][37][38][39][40][41][42] . Recently, Kosaka and Ochiya et al suggested a novel mechanism -that miRNAs could facilitate the system of maintenance and surveillance against cancer progression.…”
mentioning
confidence: 99%
“…As indicated by the usefulness of cell-free DNA and circulating tumor cells, the concept of "liquid biopsy" through circulating miRNAs may also provide ideal individualized therapeutic strategies for cancer patients and contribute to the development of precision medicine. Indeed, previous studies, including our own, have identified various blood-based miRNA biomarker candidates, which are useful for cancer detection, monitoring tumor dynamics, and predicting malignant potential, prognosis, and chemoresistance in cancer patients [32][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
Section: Circulating Micrornas Are a Promising Source Of Diagnostic Amentioning
confidence: 99%